(3fRgI Gdedhcs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s ((3GdTGe s)
(3ChdgG (B:s
(3GdMeO ddg eHOY GdCTjGA HMceJg CeG HYO aEfi CdaJ gPG GdcJGH hLeYJ eG ajg ef GdMce hGdBOGH HGH ai PcQ GdSja GdbGWY s
(3BNQgG (B:s
(3hdG jbGJd eG hLO Edi GdMjdI hGdNOjYI SHjdkG jYed Ydi GdeWGhdI hGdeOGaYI hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs